Teaching obstetric ultrasound at Mulago Hospital - Kampala, Uganda - Ahmadzia, Homa (Afr Health Sci, 2018)
BACKGROUND: Mulago Hospital is a high volume referral hospital under the Makerere University School of Medicine and Health Sciences. Basic obstetric ultrasound is a useful skill that can aid patient care. OBJECTIVES: The purpose of the study was to assess the effectiveness of an intervention implemented to teach basic ultrasound skills to medical students and house officers at Mulago Hosptial, Kampala, Uganda. METHODS: Forty participants, including medical students, junior house officers (JHOs), and senior house officers (SHOs) were enrolled in the study. A didactic and practical hands-on teaching session was evaluated using a pre- and post-test that was administered to all participants. RESULTS: Participants included 12 medical students, 23 JHOs, and 5 SHOs. A significant difference in pre- and post-test scores was demonstrated in the medical students and JHOs (34% to 76%, p <0.0001) and this was retained when the results were stratified into the basic definitions and practical sections of the survey (33% to 71%, p<0.0001). The scores for the senior house officers had a mean increase of 2.3 points. CONCLUSION: This original teaching intervention is an effective method to improve knowledge and skills for medical students and house officers at Mulago Hospital in the area of basic obstetric ultrasound.